(untitled) (Świat Idei i Polityki, 2006)
The welfare state, one of the most important European institutions of the 20th century, is in a serious crisis now and many experts forecast its near decline. The author of the article tries to prove the fact that there have always been many debates on the welfare state: its origin, essence, and its models. But now the welfare state is a subject of a very severe criticism. The author describes some arguments against the welfare state, especially those which underline its economic ineffectiveness. The author also presents some of its advantages. Although nowadays the attitude of most economists and politicians towards the European welfare state is negative, some positive results of its transformation in some European countries (Sweden is the best example) show that the welfare state has the chance to survive.